Method for manufacturing a welded joint by pulsed arc welding and welded joint

JP2026169050APending Publication Date: 2026-10-16NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025062710
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-04
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0020】 本発明によれば、電着塗装性や継手強度を低下させることなく、スパッタ付着量が低減された溶接継手の製造方法及び溶接継手を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026169050000001_ABST
    Figure 2026169050000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a welded joint and a welded joint in which the amount of spatter adhesion is reduced without reducing the electrodeposition coating properties or joint strength. [Solution] The present invention provides a method for manufacturing a welded joint by pulsed arc welding, characterized by performing pulsed arc welding to form a weld metal of a specific chemical composition under conditions where the wire consumption W and pulse frequency f satisfy the following formula (1). Furthermore, the present invention provides a welded joint comprising a steel plate and a weld bead, wherein the weld metal forming the weld bead has a specific chemical composition, and the amount of spatter adhering to the weld bead-side surface of the welded joint in the area surrounding the weld bead is 2.0 spatter particles / cm². 2 It is characterized by the following: 0.15 ≤ 10 × W / f ≤ 1.00 ···(1)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a welded joint by pulse arc welding, and a welded joint obtained thereby.

Background Art

[0002] Pulse arc welding is widely used in the manufacture of automotive chassis members. In recent trends, ultra-low Si solid wires are used to improve the electrodeposition coating properties and corrosion resistance of the welded portions of chassis members. Ultra-low Si solid wires function to reduce coating defects caused by welding slag.

[0003] For example, Patent Document 1 discloses an ultra-low silicon welding wire with excellent porosity resistance and electrodeposition coating properties, which contains, in mass%, C: 0.001 to 0.30%, Si: 0.001 to 0.1%, Mn: 0.50 to 3.00%, P: 0.030% or less, S: 0.030% or less, further contains one or more selected from Ni: 0.001 to 0.900%, Cr: 0.001 to 0.100%, Mo: 0.001 to 0.500%, and Cu: 0.50% or less, with the balance being Fe and unavoidable impurities.

[0004] Ultra-low Si solid wires function to reduce coating defects caused by welding slag, but on the other hand, a large amount of spatter may be generated. If a large amount of spatter adheres to the welded portion and its surroundings, the man-hours required to remove it increase, which may lead to a reduction in production efficiency.

[0005] As a technique for reducing the generation of such spatter, for example, Patent Document 2 discloses a pulse arc welding method that acquires waveform information and the amount of generated spatter when pulse arc welding is performed using a welding wire of a predetermined material, and automatically searches for a pulse waveform that further reduces the amount of spatter from these pieces of information.

Prior Art Documents

Patent Documents

[0006] [Patent Document 1] Patent No. 6829699 [Patent Document 2] Patent No. 7195993 [Overview of the Initiative] [Problems that the invention aims to solve]

[0007] Ultra-low Si solid wires can improve the electrodeposition coating properties and corrosion resistance of welded areas. On the other hand, reducing the Si content in the wire lowers the surface tension and viscosity of the molten metal, making it easier for molten droplets to stretch when they detach from the molten wire (droplet migration). This is thought to cause short circuits between the droplets and the molten pool, increasing the generation of spatter.

[0008] Therefore, even if we try to reduce spatter generation due to short circuits by optimizing the pulse current and pulse voltage of the welding power supply involved in droplet detachment (droplet transfer), simply optimizing the pulse waveform will have some spatter reduction effect, but it will not lead to a reduction in spatter that is sufficient to improve production efficiency.

[0009] This invention has been made in view of the above circumstances, and aims to provide a method for manufacturing a welded joint and a welded joint in which the amount of spatter adhesion is reduced without reducing the electrodeposition coating properties or joint strength. [Means for solving the problem]

[0010] The present invention includes the following embodiments.

[0011] (Aspect 1) A method for manufacturing welded joints by pulsed arc welding, The chemical composition is expressed in mass percent. C: 0.02~0.25%, Si: 0.02~1.50%, Mn: 0.30~3.50%, Ti: 0.04~0.25%, Al: 0.002~0.350%, O: 0.065% or less, N: 0.0350% or less, P: 0.030% or less, S: 0.020% or less, Sb: 0~0.50%, B: 0~0.0100%, Cr: 0~0.80%, Ni: 0~1.00%, Mo: 0~0.200%, V: 0~0.300%, and The remainder: Using a welding wire formed from weld metal consisting of Fe and impurities, Wire consumption W (cm) 3 A method for manufacturing a welded joint, characterized in that the pulsed arc welding described above is performed under the condition that the pulse frequency ( / min) and pulse frequency f (Hz) satisfy the following formula (1). 0.15 ≤ 10 × W / f ≤ 1.00 ···(1)

[0012] (Aspect 2) The chemical composition of the above weld metal is, in mass%, Sb: 0.01~0.50%, B: 0.0010~0.0100%, Cr: 0.01~0.80%, Ni: 0.01~1.00%, Mo: 0.001~0.200%, and V: 0.001~0.300% The manufacturing method according to embodiment 1 above, characterized by containing one or more selected from the group consisting of the above.

[0013] (Aspect 3) The peak time T in the pulsed arc welding described above. p (milliseconds), rise time T up (milliseconds) and fall time T down The manufacturing method according to embodiment 1 or 2, characterized in that (milliseconds) satisfies the following formulas (2) and (3). T p >T up ≧T down ...(2) 1.0≦T up / T down ≦3.5 ···(3)

[0014] (Aspect 4) The peak current I in the pulsed arc welding described above p is 450 to 600 A, and the base current I b is 55 A or more, the production method according to any one of the above Aspects 1 to 3.

[0015] (Aspect 5) A welded joint comprising a steel sheet and a weld bead, wherein the chemical composition of the weld metal forming the weld bead described above is, in mass%, C: 0.02 to 0.25%, Si: 0.02 to 1.50%, Mn: 0.30 to 3.50%, Ti: 0.04 to 0.25%, Al: 0.002 to 0.350%, O: 0.065% or less, N: 0.0350% or less, P: 0.030% or less, S: 0.020% or less, Sb: 0 to 0.50%, B: 0 to 0.0100%, Cr: 0 to 0.80%, Ni: 0 to 1.00%, Mo: 0 to 0.200%, V: 0 to 0.300%, and the balance: Fe and impurities, On the weld bead side surface of the welded joint described above, the spatter adhesion amount in a weld bead peripheral region that has a length of 50 mm in the longitudinal direction extending along the weld bead and a width of 100 mm in the width direction centered on the weld bead and orthogonal to the longitudinal direction is 2.0 pieces / cm 2 or less, the welded joint.

[0016] (Aspect 6) The chemical composition of the weld metal described above is, in mass%, Sb: 0.01~0.50%, B: 0.0010~0.0100%, Cr: 0.01~0.80%, Ni: 0.01~1.00%, Mo: 0.001~0.200%, and V: 0.001~0.300% The welded joint according to embodiment 5, characterized in that it contains one or more selected from the group consisting of the above.

[0017] (Aspect 7) The above spatter deposition amount is 1.0 particles / cm². 2 The welded joint according to embodiment 5 or 6 described above, characterized in that it is as follows:

[0018] (Pattern 8) The above spatter deposition amount is 0.5 particles / cm². 2 The welded joint according to embodiment 5 or 6 described above, characterized in that it is as follows:

[0019] (Aspect 9) The above sputter deposition amount is 0.1 particles / cm². 2 The welded joint according to embodiment 5 or 6 described above, characterized in that it is as follows: [Effects of the Invention]

[0020] According to the present invention, it is possible to provide a method for manufacturing a welded joint and a welded joint in which the amount of spatter adhesion is reduced without reducing the electrodeposition coating properties or joint strength. [Brief explanation of the drawing]

[0021] [Figure 1] Figure 1 shows the difference in spatter generation depending on the wire component and steel plate type. [Figure 2] Figure 2 shows the sputter suppression effect achieved by optimizing the weld metal composition and pulse waveform. [Figure 3] Figure 3 schematically shows the area surrounding the weld bead on the weld bead-side surface of a welded joint. [Modes for carrying out the invention]

[0022] To achieve the above objective, the inventors diligently investigated new methods for suppressing spatter generation. As a result, the inventors found that optimizing the weld metal composition and optimizing the pulse waveform in the welding power supply are effective in reducing spatter. Furthermore, using this finding, the inventors discovered a new method that can suppress spatter generation even when using extremely low Si solid wires, which are prone to spatter generation.

[0023] The present invention was completed based on the above findings and includes the following embodiments of the manufacturing method and welded joint.

[0024] The method for manufacturing a welded joint by pulse arc welding according to the present invention, and preferred embodiments of the welded joint obtained thereby, will be described in detail below with reference to the drawings. In this specification, unless otherwise specified, various numerical ranges mean a range including their upper and lower limits.

[0025] <Method for manufacturing welded joints> One embodiment of the present invention is a method for manufacturing a welded joint by pulsed arc welding. The manufacturing method of this embodiment has a chemical composition of mass%, C: 0.02~0.25%, Si: 0.02~1.50%, Mn: 0.30~3.50%, Ti: 0.04~0.25%, Al: 0.002~0.350%, O: 0.065% or less, N: 0.0350% or less, P: 0.030% or less, S: 0.020% or less, Sb: 0~0.50%, B: 0~0.0100%, Cr: 0~0.80%, Ni: 0~1.00%, Mo: 0~0.200%, V: 0~0.300%, and The remainder consists of Fe and impurities, forming the weld metal.

[0026] Furthermore, the manufacturing method of this embodiment has a wire consumption W(cm 3 Pulse arc welding is performed under the conditions that the pulse frequency ( / min) and pulse frequency f (Hz) satisfy the following equation (1). 0.15 ≤ 10 × W / f ≤ 1.00 ···(1)

[0027] Figure 1 shows the difference in spatter generation depending on the wire type and steel plate type. The various photographs in Figure 1 are images of the weld area taken from the front with a video camera during pulsed arc welding, and spatter is shown as high brightness. Figure 2 shows the spatter suppression effect by optimizing the weld metal component and pulse waveform.

[0028] As described above, spatter is thought to occur when molten droplets detach from the molten part of the wire (droplet migration), causing them to extend and resulting in a short circuit between the droplet and the molten pool. The inventors first attempted to reduce spatter generation due to short circuits by optimizing the pulse current and voltage waveform of the welding power supply involved in droplet detachment (droplet migration) using conventional methods. As a result, a certain spatter reduction effect was confirmed, but it was not enough to reduce spatter to the extent that it would lower production efficiency.

[0029] Therefore, as shown in Figure 1, the inventors attempted to reduce spatter by optimizing the pulse waveform in the welding power source as described above, as well as by investigating the optimal composition of the weld metal components. In Figure 1, wires A and B are both low-slag wires, and are welding wires with different components. On the other hand, steel plates A and B are steel plates with different tensile strengths and components.

[0030] As shown in Figure 1, it can be seen that spatter reduction is possible by controlling the weld metal composition formed by the steel plate and welding wire. In particular, in the example shown in Figure 1, the combination of steel plate B and wire B can reduce spatter the most, while the other combinations do not reduce spatter sufficiently because the weld metal composition is not appropriate.

[0031] On the other hand, the steel plate component is one of the factors that affect the convection of the molten pool, and the height of the molten pool directly below the arc plasma, i.e., the distance between the molten droplet at the tip of the wire and the surface of the molten pool, differs. This convection can be roughly controlled by the combination of the welding wire component and the steel plate component (i.e., the components of the weld metal), and it is thought that this resulted in the difference in the amount of spatter generated as shown in Figure 1.

[0032] Therefore, the inventors verified the sputter reduction effect by controlling the droplet transfer phenomenon as shown in Figure 2 through detailed tuning of the pulse waveform, i.e., optimization of the rising and falling edges of the pulse waveform, and increasing the pulse frequency. As a result, it was found that even with pulsed arc welding using extremely low Si welding wire, spatter can be sufficiently reduced without reducing electrodeposition coating properties or joint strength by (i) optimizing the pulse waveform in the welding power source (i.e., the wire consumption W and pulse frequency f satisfy equation (1) above) and (ii) optimizing the weld metal composition (i.e., the weld metal composition has the above-mentioned specific chemical composition).

[0033] In this embodiment, the manufacturing method involves pulse arc welding such that the weld metal components have the specific chemical composition described above, and the wire consumption W and pulse frequency f satisfy formula (1). As a result, even when using extremely low Si welding wires that are prone to spatter generation, spatter generation can be sufficiently suppressed. Consequently, a welded joint with a sufficiently reduced amount of spatter can be obtained without compromising electrodeposition coating properties or joint strength.

[0034] The welding wire used in the manufacturing method of this embodiment is not particularly limited as long as it can produce a weld metal with the above-mentioned specific chemical composition. For example, the chemical composition may be as follows: C: 0.050~0.250%, Si: 0.02~0.45%, Mn: 0.50~3.20%, Ti: 0.040~0.250%, Al: 0.002~0.350%, O: 0.065% or less, N: 0.0500% or less, P: 0.0500% or less, S: 0.020% or less, Sb: 0~0.50%, B: 0~0.0100%, Cr: 0~0.80%, Ni: 0~1.00%, Mo: 0~0.20%, V: 0~0.30%, Cu: 0~0.60%, and The remainder may be welding wire consisting of Fe and impurities.

[0035] Furthermore, the manufacturing method of this embodiment can further suppress spatter generation not only when using extremely low-Si welding wires that are prone to spatter generation, but also when using general-purpose welding wires that inherently generate less spatter.

[0036] The weld metal formed by the manufacturing method of this embodiment will be described below.

[0037] [Weld metal] In the manufacturing method of this embodiment, a weld metal having the following specific chemical composition is formed. In other words, the weld metal is, in mass%, C: 0.02~0.25%, Si: 0.02~1.50%, Mn: 0.30~3.50%, Ti: 0.04~0.25%, Al: 0.002~0.350%, O: 0.065% or less, N: 0.0350% or less, P: 0.030% or less, S: 0.020% or less, Sb: 0~0.50%, B: 0~0.0100%, Cr: 0~0.80%, Ni: 0~1.00%, Mo: 0~0.200%, V: 0~0.300%, and The remainder has a chemical composition consisting of Fe and impurities.

[0038] Weld metal is the metal that forms the weld bead in a welded joint after welding. The metal components that form the weld bead are a mixture of the metal components of the welding wire and the metal components of the steel plate.

[0039] The following provides a detailed explanation of each component of the weld metal. In the following explanation, the content of each component refers to its mass ratio relative to the total mass of the weld metal.

[0040] (C: 0.02~0.25%) Carbon (C) is an element that improves the strength of the weld metal. To ensure a certain level of strength in the weld metal, the C content should be 0.02% or higher. To further improve the strength of the weld metal, the lower limit of the C content may be 0.04%, 0.05%, or 0.06%. In addition, to prevent the phenomenon of excessive spatter during droplet transfer due to the generation of CO gas during welding, known as explosive transfer, the C content should be 0.25% or lower. To further reduce spatter generation, the upper limit of the C content may be 0.20% or 0.15%.

[0041] (Si: 0.02~1.50%) Si is a deoxidizing element that reduces the amount of oxygen in the weld metal, thereby improving its cleanliness. Si also increases the surface tension and viscosity of the molten metal during welding. If the Si content is too low, the surface tension and viscosity of the molten metal decrease, which can lead to increased spatter, or so-called short-circuit transfer. Therefore, the Si content should be 0.02% or higher. To further reduce spatter, the lower limit of the Si content may be 0.04%, 0.06%, or 0.08%. Conversely, if the Si content is too high, the electrodeposition coating properties may deteriorate. Therefore, the Si content should be 1.50% or lower. To further improve the electrodeposition coating properties, the upper limit of the Si content may be 1.40%, 1.20%, 1.00%, or 0.80%.

[0042] (Mn: 0.30~3.50%) Mn is an element that ensures the hardenability of weld metal and increases its strength. To ensure a certain level of strength in the weld metal, the Mn content should be 0.30% or higher. To further improve the strength of the weld metal, the lower limit of the Mn content may be 0.50%, 0.80%, or 1.00%. Furthermore, if the Mn content is excessively high, the electrodeposition coating properties may deteriorate due to the coordinated deoxidation of Si and Mn (i.e., increased deoxidation effect of Si). For this reason, the Mn content should be 3.50% or lower. To further improve the electrodeposition coating properties, the upper limit of the Mn content may be 3.30%, 3.00%, 2.80%, or 2.50%.

[0043] (Ti: 0.04~0.25%) Ti is an effective deoxidizing element, reducing the amount of oxygen in the weld metal. It is also an effective element for fixing solid-solution nitrogen and mitigating its adverse effect on toughness. If the Ti content is too low, it may lead to a decrease in toughness due to insufficient deoxidation of the weld metal and deterioration of electrodeposition coating properties. Therefore, the Ti content should be 0.04% or higher. To further improve the toughness and electrodeposition coating properties of the weld metal, the lower limit of the Ti content may be 0.06%, 0.08%, 0.10%, or 0.12%. In addition, to prevent excessive hardening of the weld metal, the Ti content should be 0.25% or lower. To optimize the hardness of the weld metal, the upper limit of the Ti content may be 0.24%, 0.22%, 0.20%, or 0.18%.

[0044] (Al: 0.002~0.350%) Al is a deoxidizing element and is effective in reducing the amount of oxygen in the weld metal and improving the cleanliness of the weld metal. If the Al content is too low, it may lead to a decrease in toughness due to insufficient deoxidation of the weld metal. Therefore, the Al content should be 0.002% or higher. To further improve the toughness of the weld metal, the lower limit of the Al content may be 0.005%, 0.010%, 0.015%, or 0.020%. Also, if the Al content is too high, it may lead to an increase in spatter (short circuits) due to excessive deoxidation of the weld metal. Therefore, the Al content should be 0.350% or lower. To further reduce spatter, the upper limit of the Al content may be 0.300%, 0.250%, or 0.200%.

[0045] (O: 0.065% or less) Oxygen (O) is an unavoidable component in weld metal. If the O content is excessively high, the surface tension (convection) of the molten metal may increase due to excess oxygen, which can lead to increased spatter (short circuits). Therefore, the O content should be 0.065% or less. To further reduce spatter, the upper limit of the O content may be 0.060%, 0.055%, or 0.050%. The O content may also be 0%, but from the perspective of the limit of deoxidation ability (oxygen reduction ability) in MAG (Metal Active Gas) welding, it may be 0.001% or more. To more reliably improve the toughness of the weld metal, the lower limit of the O content may be 0.002% or 0.003%.

[0046] (N:0.0350% or less) Nitrogen (N) is an unavoidable component in weld metal. Excessively high N content reduces joint strength due to nitrogen blowholes; therefore, the N content should be 0.0350% or less. To further improve joint strength, the upper limit of the N content may be 0.0300%, 0.0250%, or 0.0200%. Furthermore, a lower N content is preferable. While the lower limit of the N content may be 0%, achieving 0% N content is industrially difficult. Therefore, the practical lower limit of the N content is 0.0010% or 0.0020%.

[0047] (P:0.030% or less) P is an impurity element that reduces both the toughness and ductility of the weld metal, so it is preferable to reduce the P content as much as possible. The P content should be 0.030% or less. To further improve the toughness and ductility of the weld metal, the upper limit of the P content may be 0.025%, 0.020%, or 0.015%. The lower limit of the P content may be 0%, but it is industrially difficult to achieve a P content of 0%. Therefore, in reality, the lower limit of the P content may be 0.005% or 0.010%.

[0048] (S:0.020% or less) S is an impurity element. If the S content is excessively high, sputtering (short circuits) may increase due to an increase in the surface tension (convection) of the molten metal. Therefore, the S content should be 0.020% or less. To further reduce sputtering, the upper limit of the S content may be 0.018%, 0.016%, 0.014%, or 0.012%. The lower limit of the S content may be 0%, but achieving a 0% S content is industrially difficult. Therefore, in practice, the lower limit of the S content may be 0.001% or 0.003%.

[0049] (Sb: 0~0.50%) Sb is an element that increases the surface tension of the molten metal and promotes convection. The Sb content may be 0%, but to obtain the above effect sufficiently, the Sb content may be 0.01% or more. The lower limit of the Sb content may be 0.03%, 0.05%, or 0.10%. Furthermore, if the Sb content is excessively high, sputtering (short circuits) may increase due to the increase in the surface tension (convection) of the molten metal. For this reason, the Sb content should be 0.50% or less. To further reduce sputtering, the upper limit of the Sb content may be 0.45%, 0.40%, or 0.35%.

[0050] (B: 0~0.0100%) B is an element effective in increasing the strength of weld metal. The B content may be 0%, but to fully obtain the above effect, the B content may be 0.0010% or more. The lower limit of the B content may be 0.0020% or 0.0030%. Furthermore, to prevent excessive hardening of the weld metal, the B content should be 0.0100% or less. To optimize the hardness of the weld metal, the upper limit of the B content may be 0.0090% or 0.0080%.

[0051] (Cr: 0~0.80%) Cr enhances the hardenability of the weld metal, making it an effective element for increasing the strength of the weld metal and also effective in reducing spatter. The Cr content may be 0%, but to fully obtain the above effects, the Cr content may be 0.01% or more. The lower limit of the Cr content may be 0.05% or 0.10%. Furthermore, to prevent excessive hardening of the weld metal, the Cr content should be 0.80% or less. To optimize the hardness of the weld metal, the upper limit of the Cr content may be 0.75% or 0.70%.

[0052] (Ni: 0~1.00%) Ni is an element that enhances the toughness of the weld metal through solid solution and is also effective in reducing spatter. The Ni content may be 0%, but to fully obtain the above effects, the Ni content may be 0.01% or more. The lower limit of the Ni content may be 0.05% or 0.10%. Furthermore, to prevent welding cracks, the Ni content should be 1.00% or less. To more reliably prevent welding cracks, the upper limit of the Ni content may be 0.95%, 0.90%, 0.85%, or 0.80%.

[0053] (Mo: 0~0.200%) Mo is an element that enhances the hardenability of weld metal and is also effective in ensuring tensile strength through precipitation strengthening by forming fine carbides. The Mo content may be 0%, but to fully obtain the above effects, the Mo content may be 0.001% or more. The lower limit of the Mo content may be 0.005%, 0.010%, 0.015%, or 0.020%. Furthermore, to prevent excessive hardening of the weld metal, the Mo content should be 0.200% or less. To optimize the hardness of the weld metal, the upper limit of the Mo content may be 0.180%, 0.160%, or 0.150%.

[0054] (V: 0~0.300%) V enhances the hardenability of the weld metal, making it an effective element for increasing the strength of the weld metal. The V content may be 0%, but to fully obtain the above effect, the V content may be 0.001% or more. The lower limit of the V content may be 0.005%, 0.010%, 0.015%, or 0.020%. Furthermore, to prevent excessive hardening of the weld metal, the V content should be 0.300% or less. To optimize the hardness of the weld metal, the upper limit of the V content may be 0.280%, 0.260%, or 0.250%.

[0055] In this embodiment, the chemical composition of the weld metal is, in mass%, Sb: 0.01~0.50%, B: 0.0010~0.0100%, Cr: 0.01~0.80%, Ni: 0.01~1.00%, Mo: 0.001~0.200%, and V: 0.001~0.300% It may also contain one or more selected from the group consisting of the following:

[0056] (Remainder) The remainder of the weld metal, excluding the above-mentioned components, consists of Fe and impurities. Examples of impurities include As and Bi.

[0057] Furthermore, the aforementioned C, Si, Mn, Cr, Ni, Mo, and V do not necessarily have to be pure substances; they may be present in the weld metal in the form of alloys such as Cu-Ni.

[0058] The chemical composition of the weld metal (i.e., the weld bead) can be measured using general analytical methods. For example, the chemical composition of the weld metal can be measured using inductively coupled plasma-atomic emission spectrometry (ICP-AES). Specifically, about 5 g of metal powder is taken from the portion of the weld bead excluding the beginning (the portion up to 15 mm from the beginning end) and the end (the portion up to 15 mm from the end end), and the chemical composition of the weld metal can be determined by measuring this metal powder using a measuring device such as the Shimadzu ICPS-8100 under conditions based on a pre-established calibration curve. C and S, which cannot be measured by ICP-AES, can be measured using combustion-infrared absorption spectroscopy, N can be measured using inert gas fusion-thermal conductivity spectroscopy, and O can be measured using inert gas fusion-nondispersive infrared absorption spectroscopy.

[0059] In this embodiment, pulse arc welding is performed using a predetermined welding wire to form a weld metal (weld bead) having the above-mentioned specific chemical composition. The welding conditions for pulse arc welding in this embodiment will be described in detail below.

[0060] [Pulse arc welding] In this embodiment, pulse arc welding using the welding wire described above consumes a wire W(cm 3 The procedure must be performed under the condition that the pulse frequency ( / min) and pulse frequency f (Hz) satisfy the following equation (1). 0.15 ≤ 10 × W / f ≤ 1.00 ···(1)

[0061] If 10 × W / f in formula (1) above is less than 0.15, the size of the molten droplets during welding may become excessively small, resulting in an irregular weld bead. On the other hand, if 10 × W / f exceeds 1.00, the size of the molten droplets during welding may become excessively large, resulting in a lot of spatter. In formula (1) above, 10 × W / f is preferably 0.18 or higher, more preferably 0.20 or higher, and even more preferably 0.25 or higher. Furthermore, 10 × W / f is preferably 0.95 or lower, more preferably 0.90 or lower, and even more preferably 0.80 or lower.

[0062] [Welding conditions] In this embodiment, the wire consumption W, pulse frequency f, and peak time T in the pulse waveform of pulse arc welding using the welding wire described above are also considered. p , Startup time T up , fall time T down Peak current I p Base current I b The preferred ranges for various welding conditions are set for each prerequisite heat input condition, with the aim of ensuring that molten droplets are of an appropriate size and suppressing the generation of irregular beads and spatter.

[0063] The following describes the preferred ranges for various welding conditions in this embodiment, for each heat input condition: low heat input for steel plate thicknesses of approximately 1.6 mm, standard heat input for approximately 2.3 mm, and high heat input for 3.2 mm. Note that the guideline for low heat input is the average welding current I ave The average welding current is 100-180A, and the average welding current V ave The voltage is 22.0V, and the welding speed V is 40-130cm / min. The standard heat input guideline is the average welding current I ave The average welding current is 180-260A, and the average welding current V ave The voltage is 25.0V, and the welding speed V is 50-180cm / min. The guideline for high heat input is the average welding current I ave The average welding current is 260-320A, and the average welding current V ave The voltage is 28.0V, and the welding speed V is 60-200cm / min.

[0064] (Wire consumption watts) In this embodiment, the preferred range for wire consumption W is 3.0 to 6.5 cm in the case of low heat input. 3 This is per minute, and under standard heat input conditions, it is 6.5-10.0 cm. 3 The rate is per minute, and in the case of high heat input, it is 10.0-17.0 cm. 3 It is per minute.

[0065] (Pulse frequency f) In this embodiment, the preferred range of pulse frequency f is 100 to 200 Hz for low heat input, 120 to 250 Hz for standard heat input, and 150 to 280 Hz for high heat input.

[0066] Furthermore, in this embodiment, the peak time T in pulsed arc welding p (milliseconds), rise time T up (milliseconds) and fall time T down (Milliseconds) preferably satisfies the following equations (2) and (3). T p >T up ≧T down ...(2) 1.0 ≤ T up / T down ≤3.5 ···(3)

[0067] Peak time T p , Startup time T up and fall time T down If the above equation (2) is satisfied, it is easier to secure the energy necessary for droplet formation, making it easier to form droplets of the appropriate size and to stabilize droplet migration. Furthermore, the rise time T up and fall time T down If the above equation (3) is satisfied, the droplet transfer becomes more stable. Therefore, peak time T p , Startup time T up and fall time T down If the above equations (2) and (3) are satisfied, the occurrence of irregular beads and spatter can be suppressed more reliably.

[0068] Note that T in equation (3) up / T down It is preferably 1.3 or higher, and more preferably 1.5 or higher. up / T down It is preferably 3.3 or less, and more preferably 3.0 or less.

[0069] (Peak time T) p ) In this embodiment, the peak time T p The preferred range is 1.0 to 3.0 milliseconds for low heat input, standard heat input, and high heat input.

[0070] (Startup time T) up ) In this embodiment, the rise time T up The preferred range is 0.5 to 2.0 milliseconds for low heat input, standard heat input, and high heat input.

[0071] (fall time T) down ) In this embodiment, the fall time T down The preferred range is 0.3 to 1.8 milliseconds for low heat input, standard heat input, and high heat input.

[0072] Furthermore, in this embodiment, the peak current I in pulsed arc welding p The current is 450-600A, and the base current I b It is preferable that the current is 55A or higher.

[0073] (Peak current I p ) In this embodiment, the peak current I p The preferred range is 450-600A, as described above. This preferred range is common to all cases: low heat input, standard heat input, and high heat input. Peak current I p If the current is 450A or higher, it becomes easier to secure the energy necessary for droplet formation, and droplet migration becomes more stable. On the other hand, the peak current I p If the current is 600A or less, the droplet size is less likely to enlarge, and sputtering (short circuits) becomes less likely to occur.

[0074] (Base current I b ) In this embodiment, base current I bThe preferred range is 55A or higher, as described above. This preferred range is common to all cases of low heat input, standard heat input, and high heat input, however, in the case of low heat input, 45A or higher is also a sufficiently preferred range, and in the case of standard heat input, 50A or higher is also a sufficiently preferred range. Base current I b If the input is above these lower limits (i.e., 45A for low heat input, 50A for standard heat input, and 55A for high heat input), the increase in sputtering due to magnetic blowing becomes easier to suppress.

[0075] As described above, the manufacturing method of this embodiment can sufficiently suppress the generation of spatter not only when using general-purpose welding wire, but also when using extremely low Si welding wire, which is prone to spatter generation. Therefore, the welded joint obtained by the manufacturing method of this embodiment is a welded joint in which the amount of spatter adhering to the area around the double weld bead is sufficiently reduced. This welded joint is also one embodiment of the present invention.

[0076] The following describes in detail another embodiment of the present invention, a welded joint.

[0077] <Welded joints> A welded joint according to one embodiment of the present invention is a welded joint comprising a steel plate and a weld bead. In this embodiment, the chemical composition of the weld metal forming the weld bead is, by mass%, C: 0.02~0.25%, Si: 0.02~1.50%, Mn: 0.30~3.50%, Ti: 0.04~0.25%, Al: 0.002~0.350%, O: 0.065% or less, N: 0.0350% or less, P: 0.030% or less, S: 0.020% or less, Sb: 0~0.50%, B: 0~0.0100%, Cr: 0~0.80%, Ni: 0~1.00%, Mo: 0~0.200%, V: 0~0.300%, and The remainder consists of Fe and impurities.

[0078] Furthermore, in this embodiment, the amount of spatter adhering to the weld bead-side surface in the area surrounding the weld bead is 2.0 spatter particles / cm². 2 The following applies:

[0079] Here, Figure 3 is a schematic diagram showing the area around the weld bead on the weld bead-side surface of a welded joint. As shown in Figure 3, the area around the weld bead 3 on the weld bead-side surface of the welded joint 1 is an area with a length D1 in the longitudinal direction extending along the weld bead 2 of 50 mm, and a length D2 in the width direction that is centered on the weld bead 2 and perpendicular to the longitudinal direction D1 of 100 mm.

[0080] Furthermore, the spatter particles that are measured as the amount of spatter adhesion are large spatter particles that need to be removed, i.e., spatter particles that are large enough to reduce production efficiency, and whose maximum particle size in a plan view is 0.5 mm or larger. Regarding the maximum particle size of spatter in a plan view, the particle shape of spatter adhering to the weld bead side surface is usually irregular, and it may take the form of clumps formed by the bonding of two or more particles. However, regardless of the form, a spatter particle or clump that is separated from other particles or clumps and partitioned as a single clump is considered as one spatter particle, and the diameter of the circumscribed circle of that single spatter particle when viewed in a plan view is taken as the maximum spatter particle size.

[0081] Therefore, the above spatter adhesion amount is the amount of spatter with a maximum particle size of 0.5 mm or larger that adheres to the weld bead side surface in the area surrounding the weld bead of the weld joint, per unit area (1 cm²). 2 This refers to the number of items per unit.

[0082] In this embodiment, the welded joint is characterized in that the weld metal forming the weld bead has the above-mentioned specific chemical composition, and the amount of spatter adhering to the area surrounding the weld bead is 2.0 particles / cm². 2As a result of the following, this welded joint offers excellent production efficiency during manufacturing, as well as superior electrodeposition coating properties and corrosion resistance.

[0083] (Method for measuring the amount of sputter adhesion) The amount of sputter deposition can be measured as follows. First, the area surrounding the weld bead on the weld bead side surface of the weld joint to be measured is observed using various cameras, microscopes, optical microscopes, electron microscopes, and other magnification observation methods, and the number of spatter particles with a maximum particle size of 0.5 mm or more within a predetermined area is measured. Next, the number of measured spatter particles is divided by the predetermined area to obtain the number of spatter particles per unit area (particles / cm²). 2 Calculate ).

[0084] In this embodiment, the amount of spatter adhering to the area around the weld bead of the welded joint is 1.0 spatter particles / cm². 2 Preferably, it is 0.5 pieces / cm 2 It is more preferable that the following conditions are met: 0.1 pieces / cm 2 The following is even more preferable:

[0085] Next, the weld metal that forms the weld bead of the welded joint in this embodiment will be described.

[0086] (Weld metal) In the welded joint of this embodiment, the chemical composition of the weld metal forming the weld bead is, in mass%, C: 0.02~0.25%, Si: 0.02~1.50%, Mn: 0.30~3.50%, Ti: 0.04~0.25%, Al: 0.002~0.350%, O: 0.065% or less, N: 0.0350% or less, P: 0.030% or less, S: 0.020% or less, Sb: 0~0.50%, B: 0~0.0100%, Cr: 0~0.80%, Ni: 0~1.00%, Mo: 0~0.200%, V: 0~0.300%, and The remainder consists of Fe and impurities.

[0087] The components of the weld metal forming the weld bead described above are the same as those of the weld metal formed by the manufacturing method of the embodiment described above, so their explanation will be omitted.

[0088] Furthermore, the chemical composition of the weld metal forming the weld bead is expressed in mass percent. Sb: 0.01~0.50%, B: 0.0010~0.0100%, Cr: 0.01~0.80%, Ni: 0.01~1.00%, Mo: 0.001~0.200%, and V: 0.001~0.300% It may also contain one or more selected from the group consisting of the following:

[0089] Next, the steel plate in the welded joint of this embodiment will be described.

[0090] [Steel plate] In this embodiment, the steel plate to be welded is not particularly limited, and any steel plate can be used depending on the type of part to which the welded joint is applied (e.g., an automobile chassis member). Examples of such steel plates include steel plates having a predetermined tensile strength.

[0091] The tensile strength (TS) of a steel sheet is not particularly limited, but examples include tensile strengths of 780 MPa or higher, 980 MPa or higher, 1200 MPa or higher, 1500 MPa or higher, or 1800 MPa or higher. The upper limit of the tensile strength of a steel sheet is not particularly limited, but for workability and other reasons, it is, for example, 3000 MPa. The tensile strength of a steel sheet is measured by taking a No. 5 tensile test specimen of JIS Z2241:2011 from the steel sheet, with the longitudinal direction perpendicular to the rolling direction and the thickness direction, and performing a tensile test in accordance with JIS Z2241:2011.

[0092] The thickness of the steel plate is not particularly limited, and a thickness can be adopted according to the type of part to which the welded joint is applied (for example, automobile chassis components). Examples of such thicknesses include 1 mm or more, 1.5 mm or more, or 2 mm or more. Alternatively, the thickness of the steel plate may be, for example, 10 mm or less, 8 mm or less, or 6 mm or less.

[0093] Furthermore, in this embodiment, the chemical composition of the steel sheet that can be used as the material to be welded is not particularly limited as long as it yields a weld metal with the specific chemical composition described above. Examples of the chemical composition of the steel sheet include the following: In other words, the steel plate that can be used in this embodiment is, by mass%, C: 0.050~0.200%, Si: 0.02~0.15%, Mn: 0.50~3.00%, Al: 0.002~0.400%, N: 0.0010~0.0070%, P:0.0060% or less, S: 0.004% or less, O: 0.005% or less, Ti: 0~0.010%, Ni: 0-2.50%, Mo: 0~0.80%, V: 0~0.07%, Sb: 0~0.50%, B: 0~0.0080%, Cu: 0~1.00%, Cr: 0~0.80%, Nb: 0~0.030%, Ca: 0~0.0030%, Mg: 0~0.0030%, REM: 0~0.0030%, and The remainder may be a steel sheet having a chemical composition of Fe and impurities.

[0094] The following provides a detailed explanation of each component that makes up such steel plates.

[0095] (C: 0.050~0.200%) Carbon (C) is an element necessary for ensuring the strength of steel plates. To obtain this effect sufficiently, the C content may be 0.050% or more. The C content may also be 0.080% or more. On the other hand, excessive C content may lead to coarsening of grain boundary carbides. Therefore, the C content may be 0.200% or less. The C content may also be 0.150% or less.

[0096] (Si: 0.02~0.15%) Si is a deoxidizing element in steel and is effective in increasing the strength of steel sheets without impairing their ductility. To obtain these effects fully, the Si content may be 0.02% or more. The Si content may also be 0.05% or more. On the other hand, if the Si content is excessive, scale will remain in a striped pattern, degrading the appearance of the steel sheet surface. Therefore, the Si content may be 0.15% or less. The Si content may also be 0.14% or less.

[0097] (Mn: 0.50~3.00%) Mn is an element necessary for ensuring the strength of steel sheets. To obtain this effect sufficiently, the Mn content may be 0.50% or more. The Mn content may also be 0.55% or more, or 0.60% or more. On the other hand, if the Mn content is excessive, microsegregation and macrosegregation are more likely to occur, which may reduce the workability of the steel sheet. Therefore, the Mn content may be 3.00% or less. The Mn content may also be 2.50% or less, or 2.00% or less.

[0098] (Al: 0.002~0.400%) Al is an element that functions as a deoxidizing agent and is effective in increasing the strength of steel plates. To obtain this effect sufficiently, the Al content may be 0.002% or more. The Al content may also be 0.020% or more, or 0.030% or more. On the other hand, if Al is present in excess, it may combine with N to form nitrides, which may reduce the fatigue strength of welded joints. Therefore, the Al content may be 0.400% or less. The Al content may also be 0.350% or less, or 0.300% or less.

[0099] (N: 0.0010~0.0070%) N is an element that inevitably gets mixed in during steel refining. The N content may be 0%, but since reducing the N content to less than 0.0015% increases manufacturing costs, it is preferable to set the N content at a lower limit of 0.0010%. The N content may be 0.0020% or more, or 0.0025% or more. On the other hand, since N can form nitrides and degrade workability, the N content may be 0.0070% or less. The N content may be 0.0065% or less, or 0.0060% or less.

[0100] (P:0.0060% or less) P is an element that inevitably gets mixed in during steel refining. The P content may be 0%, but reducing the P content to less than 0.0001% would increase the cost of dephosphorization, so it is preferable to set the P content to a lower limit of 0.0001%. The P content may be 0.0005% or more, or 0.0010% or more. On the other hand, if the P content exceeds 0.0060%, solidification segregation during casting becomes significant, which can lead to internal cracking and reduced workability, as well as embrittlement of the weld. Therefore, the P content may be 0.0060% or less. The P content may also be 0.0050% or less, or 0.0030% or less.

[0101] (S :0.004% or less) S is an element that inevitably gets mixed in during steel refining. The S content may be 0%, but since reducing the S content to less than 0.0001% increases manufacturing costs, it is preferable to set the S content at a lower limit of 0.0001%. The S content may be 0.0005% or more, or 0.001% or more. On the other hand, S may combine with Mn and Ti to form precipitates, which can reduce workability. Therefore, the S content may be 0.004% or less. The S content may be 0.003% or less, or 0.002% or less.

[0102] (O: 0.005% or less) O is an element that inevitably gets mixed in during steel refining. The O content may be 0%, but since reducing the O content to less than 0.0001% increases manufacturing costs, it is preferable to set the O content at a lower limit of 0.0001%. The O content may be 0.0005% or more, or 0.001% or more. On the other hand, O can form coarse oxides, which can degrade workability. Therefore, the O content may be 0.005% or less. The O content may be 0.004% or less, or 0.003% or less.

[0103] The basic chemical composition of an example of a steel sheet that can be used in this embodiment is as described above. Furthermore, in this embodiment, the steel sheet may contain one or more of the following optional elements in place of a portion of the remaining Fe, as needed. These optional elements will be described in detail below.

[0104] (Ti: 0~0.010%) Ti is an element that reduces the amount of S, N, and O, which generate coarse inclusions that act as fracture initiation points. Ti is also an effective element for refining the microstructure and improving the balance between strength and formability of steel sheets. While the Ti content may be 0%, it may be 0.0001% or higher to fully obtain these effects. The Ti content may be 0.0005% or higher, or 0.001% or higher. On the other hand, excessive Ti content can lead to the formation of coarse Ti sulfides, Ti nitrides, and / or Ti oxides, reducing the formability of the steel sheet. Therefore, the Ti content may be 0.010% or less. The Ti content may also be 0.008% or less, 0.006% or less, or 0.005% or less.

[0105] (Ni: 0~2.50%) Ni is an element that suppresses phase transformation at high temperatures, contributing to improved strength of steel sheets, and also improves toughness. The Ni content may be 0%, but to obtain these effects sufficiently, the Ni content may be 1.00% or more. The Ni content may be 1.20% or more, or 1.40% or more. On the other hand, excessive Ni content may reduce the weldability of the steel sheet. Therefore, the Ni content may be 2.50% or less. The Ni content may be 2.40% or less, 2.20% or less, or 2.00% or less.

[0106] (Mo: 0~0.80%) Mo is an element that suppresses phase transformation at high temperatures and contributes to improving the strength of steel sheets. The Mo content may be 0%, but to obtain this effect sufficiently, the Mo content may be 0.20% or more. The Mo content may be 0.25% or more, or 0.30% or more. On the other hand, if the Mo content is excessive, the workability may decrease and productivity may decrease. Therefore, the Mo content may be 0.80% or less. The Mo content may be 0.75% or less, or 0.70% or less.

[0107] (V: 0~0.07%) V is an element that contributes to improving the strength of steel sheets due to strengthening by precipitates, strengthening by refining through suppression of ferrite grain growth, and / or dislocation strengthening through suppression of recrystallization. The V content may be 0%, but to obtain these effects sufficiently, the V content may be 0.005% or more. The V content may be 0.01% or more, or 0.02% or more. On the other hand, if the V content is excessive, the formability of the steel sheet may decrease. Therefore, the V content may be 0.07% or less. The V content may be 0.06% or less, or 0.05% or less. (Sb: 0~0.50%) Sb is an element present when scrap is used as a raw material for steel, and a lower amount is preferable. The Sb content may be 0%, but since reducing the Sb content to less than 0.001% increases manufacturing costs, the Sb content may be 0.001% or more. The Sb content may be 0.002% or more, 0.003% or more, or 0.005% or more. On the other hand, if the Sb content exceeds 0.50%, it may lead to embrittlement of the steel sheet and a decrease in ductility. Therefore, the Sb content should be 0.50% or less. The Sb content may be 0.45% or less, 0.40% or less, or 0.35% or less.

[0108] (B: 0~0.0030%) B is an element that suppresses phase transformation at high temperatures and contributes to improving the strength of steel sheets. The B content may be 0%, but to obtain this effect sufficiently, the B content may be 0.0005% or more. The B content may be 0.0008% or more, or 0.0010% or more. On the other hand, if the B content is excessive, B precipitates may form, which may reduce the strength of the steel sheet. Therefore, the B content may be 0.0030% or less. The B content may be 0.0025% or less, or 0.0020% or less.

[0109] (Cu: 0~1.00%) Cu is an effective element for improving hardenability and ensuring the desired high strength. The Cu content may be 0%, but to fully obtain these effects, the Cu content may be 0.001% or more. The Cu content may be 0.005% or more, or 0.01% or more. On the other hand, the above effects will saturate if the Cu content is excessive. Therefore, the Cu content may be 1.00% or less. The Cu content may be 0.95% or less, 0.90% or less, 0.85% or less, or 0.80% or less.

[0110] (Cr: 0~0.80%) Cr is an element that contributes to improving the strength of steel plates and the fatigue strength of welded joints. The Cr content may be 0%, but to obtain such effects fully, the Cr content may be 0.10% or more. The Cr content may be 0.15% or more, 0.20% or more, 0.25% or more, or 0.30% or more. On the other hand, if the Cr content is excessive, there is a risk of forming coarse Cr carbides that can become fracture initiation points. Therefore, the Cr content may be 0.80% or less. The Cr content may be 0.75% or less, or 0.70% or less.

[0111] (Nb: 0~0.030%) Nb is an element that contributes to improving the strength of steel sheets due to strengthening by precipitates, strengthening by refining through suppression of ferrite grain growth, and / or dislocation strengthening through suppression of recrystallization. The Nb content may be 0%, but to obtain these effects fully, the Nb content may be 0.001% or more. The Nb content may be 0.005% or more, 0.008% or more, or 0.010% or more. On the other hand, if the Nb content is excessive, the amount of unrecrystallized ferrite may increase, which may reduce the formability of the steel sheet. Therefore, the Nb content may be 0.030% or less. The Nb content may be 0.025% or less, or 0.020% or less.

[0112] (Ca: 0~0.0030%) (Mg: 0~0.0030%) (REM: 0~0.0030%) Ca functions as a deoxidizing and desulfurizing agent, reducing the dissolved oxygen and sulfur content of molten steel. Mg and REM are dispersed as oxides and contribute to improving the toughness of steel plates and welds. Mg and REM also contribute to improving toughness through sulfide inclusions. The Ca, Mg, and REM content may be 0%, but to fully obtain the above effects, the Ca, Mg, and REM content may be 0.0001% or more. The Ca, Mg, and REM content may be 0.0005% or more, or 0.0010% or more, respectively. On the other hand, the above effects saturate if Ca, Mg, and REM are present in excessive amounts. Therefore, the Ca, Mg, and REM content may be 0.0030% or less, respectively. The Ca, Mg, and REM content may be 0.0025% or less, or 0.0020% or less, respectively.

[0113] (Remainder: Fe and impurities) The remainder of the steel plate, excluding the above-mentioned components, consists of Fe and impurities.

[0114] The chemical composition of steel plates can be measured using general analytical methods, similar to the chemical composition of weld metal described above. For example, the chemical composition of steel plates can be measured using inductively coupled plasma-atomic emission spectrometry (ICP-AES). Specifically, in the case of steel plates, a 35 mm square test piece is taken from approximately half the thickness of the steel plate, and the chemical composition of the steel plate can be determined by measuring it using a measuring device such as the Shimadzu ICPS-8100 under conditions based on a pre-established calibration curve. C and S, which cannot be measured by ICP-AES, can be measured using the combustion-infrared absorption method, N can be measured using the inert gas fusion-thermal conductivity method, and O can be measured using the inert gas fusion-nondispersive infrared absorption method.

[0115] In this embodiment, the form of the welded joint is not particularly limited, and the welded joint can be of a form that suits the desired joint strength, application, etc. Examples of such welded joints include lap fillet joints, butt joints, and T-fillet joints.

[0116] (Examples of application) The welded joints obtained by the manufacturing method of the present invention have excellent production efficiency during manufacturing, as well as excellent electrodeposition coating properties and corrosion resistance. Therefore, they can be applied not only to the chassis members of automobiles mentioned above, but also to various structural elements of buildings; various structural components of transportation machinery such as automobiles, aircraft, and ships (e.g., tanks); and various structural components of industrial machinery.

[0117] The manufacturing method and the welded joint obtained therefrom of the present invention are not limited to the embodiments described above or the examples described later, and can be appropriately combined, substituted, or modified without departing from the purpose and spirit of the present invention. [Examples]

[0118] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to such examples.

[0119] (Fabrication of welded joints) To verify the effects of the present invention, various welded joints were fabricated as follows. First, using steel plates having the chemical composition shown in Table 1 and welding wires having the chemical composition shown in Table 2, weld metal having the chemical composition shown in Table 3 was formed, and pulsed arc welding was performed under the welding conditions shown in Table 4.

[0120] In this manner, welded joints No. 1 to No. 8, which are embodiments of the present invention, and welded joints No. 9 to No. 26, which are comparative examples, were fabricated.

[0121] For welded joints No. 1 to 26, which were prepared as described above, the amount of spatter adhesion was measured according to the spatter adhesion measurement method described above, and the electrodeposition coating properties and joint strength were evaluated according to the respective evaluation methods for electrodeposition coating properties and joint strength described below. The measurement results and evaluation results are shown in Table 4 below.

[0122] (Method for evaluating electrodeposition coating properties) The weld bead of a welded joint after electrodeposition coating is photographed from above, and the area of ​​the weld bead and the area of ​​coating defects due to slag are calculated from the photographic image. The area of ​​the weld bead is calculated visually based on the contour (undulation) of the formed weld bead. The area of ​​paint defects caused by slag is determined by visually identifying the slag outline or by binarization processing, and then calculating the area based on that outline. The area of ​​the weld bead, calculated as described above, is divided by the area of ​​paint defects caused by slag, and the result is multiplied by 100 to calculate the paint defect area percentage (%).

[0123] Furthermore, if the percentage of the measured area of ​​defective coating is 10% or less, it is evaluated as having excellent electrodeposition coating properties, and if it exceeds 10%, it is evaluated as having poor electrodeposition coating properties.

[0124] (Method for evaluating joint strength) In each of the following evaluations (1) to (3), a joint will be deemed unacceptable if at least one of the following occurs: a decrease in joint strength, a decrease in toughness, or a welding defect (irregular bead).

[0125] (1) Strength evaluation of joints To evaluate the strength of the joint, first, a tensile test specimen is taken from the fabricated joint (lap fillet joint), with the weld bead as the center, the longitudinal direction being perpendicular to the direction in which the weld bead extends, and the width direction being the same direction in which the weld bead extends. The tensile test specimen has a longitudinal length of 180 mm and a width of 25 mm. Using this tensile test specimen, a tensile test is performed at a tensile speed of 10 mm / min to measure the tensile strength (MPa) of the joint. Separately, a tensile test specimen of the same shape as above is taken from the base material (steel plate) that constitutes the joint, and a tensile test is performed under the same conditions as above to measure the tensile strength (MPa) of the steel plate. Furthermore, if the tensile strength of the joint falls below 40% of the tensile strength of the steel plate, it is determined that the strength of the joint has decreased.

[0126] (2) Evaluation of the toughness of the joint To evaluate the toughness of the joint, first, a Charpy impact test specimen (V-notch specimen) is taken from the fabricated joint in accordance with JIS Z3111-2005 (Tensile and impact testing method for weld metal). A Charpy impact test is then performed at -60°C using the collected Charpy impact specimen, and the absorbed energy is measured. Furthermore, if the absorbed energy falls below 3J, it is determined that the toughness of the joint has decreased.

[0127] (3) Visual evaluation of joints The visual evaluation of the joint involves observing the weld bead of the joint and visually checking for the presence or absence of defects (irregular beads). If a defect is found in the weld bead, it is determined that there is a welding defect.

[0128] In addition, underlines next to various numerical values ​​in Tables 3 and 4 indicate that the conditions are outside the scope of the present invention or that the welded joint of the present invention cannot be obtained. In Table 4, the column for formula (2) is represented by "1" if formula (2) is satisfied and by "0" if formula (2) is not satisfied. Also in Table 4, the column for joint strength is represented by "1" if it passes and by "0" if it fails.

[0129] [Table 1]

[0130] [Table 2]

[0131] [Table 3]

[0132] [Table 4]

[0133] As shown in Tables 3 and 4, the welded joints No. 1 to No. 8, which are embodiments of the present invention, all exhibited excellent electrodeposition coating properties and joint strength, and the amount of spatter adhesion was also sufficiently reduced. On the other hand, the welded joints No. 9 to No. 26, which are comparative examples, all exhibited inferior electrodeposition coating properties, joint strength, and spatter adhesion.

[0134] Specifically, in weld joint No. 9, the carbon content in the weld metal was excessively low, resulting in softening of the weld metal due to insufficient quenching, which led to a decrease in joint strength.

[0135] In weld joint No. 10, the excessive carbon content in the weld metal resulted in the generation of CO gas, leading to frequent spatter during droplet transfer.

[0136] In welded joint No. 11, the excessively low Si content in the weld metal resulted in reduced surface tension and viscosity, leading to frequent spattering (increased short-circuit transfer).

[0137] The welded joint in No. 12 had an excessively high Si content in the weld metal, resulting in poor electrodeposition coating properties.

[0138] In welded joint No. 13, the Mn content in the weld metal was excessively low, resulting in softening of the weld metal due to insufficient quenching, which led to a decrease in joint strength.

[0139] In welded joint No. 14, the excessively high Mn content in the weld metal resulted in a deterioration of electrodeposition coating properties due to coordinated deoxidation of Si and Mn (increasing the effect of Si).

[0140] Welded joint No. 15 suffered from poor electrodeposition coating performance due to an excessively low Ti content in the weld metal.

[0141] In welded joint No. 16, the excessively high Ti content in the weld metal resulted in reduced toughness due to the formation of TiC.

[0142] In welded joint No. 17, the excessively low Al content in the weld metal resulted in reduced deoxidation capacity and consequently decreased toughness.

[0143] In weld joint No. 18, the excessively high Al content in the weld metal resulted in increased spatter due to changes in molten pool convection caused by excessive deoxidation.

[0144] In weld joint No. 19, the excessively high oxygen content in the weld metal led to increased surface tension, resulting in excessive convection of the molten metal and an increase in short-circuit spatter.

[0145] In welded joint No. 20, the excessively high nitrogen content in the weld metal resulted in nitrogen-induced blowholes and a decrease in joint strength.

[0146] In welded joint No. 21, the excessively high phosphorus content in the weld metal resulted in a decrease in the toughness of the weld metal.

[0147] In welded joint No. 22, the excessively high sulfur content in the weld metal led to increased surface tension, resulting in excessive convection of the molten metal and an increase in short-circuit spatter.

[0148] In weld joint No. 23, the excessively high Sb content in the weld metal led to increased surface tension, resulting in excessive convection of the molten metal and an increase in short-circuit spatter.

[0149] In welded joint No. 24, the excessively high content of Cr and V in the weld metal resulted in excessive hardening of the weld metal due to quenching, leading to a brittle joint strength.

[0150] In welded joint No. 25, the value of equation (1) was too small during welding, causing the molten droplets to deviate from the appropriate size, resulting in insufficient weld metal and the formation of an irregular bead.

[0151] In welded joint No. 26, the value of equation (1) was too large during welding, causing the molten droplets to enlarge beyond the appropriate size and resulting in spatter due to a short circuit. [Explanation of Symbols]

[0152] 1. Welded joint 2. Weld bead 3. Area around the weld bead D1 Length direction D2 Width direction

Claims

1. A method for manufacturing a welded joint made by pulsed arc welding, The chemical composition is expressed in mass percent. C: 0.02-0.25%, Si: 0.02-1.50%, Mn: 0.30-3.50%, Ti: 0.04-0.25%, Al: 0.002-0.350%, O: 0.065% or less, N: 0.0350% or less, P: 0.030% or less, S: 0.020% or less, Sb: 0 to 0.50%, B: 0 to 0.0100%, Cr: 0-0.80%, Ni: 0 to 1.00%, Mo: 0-0.200%, V: 0-0.300%, and The remainder: Fe and impurities form the weld metal. Wire consumption W (cm) 3 A method for manufacturing a welded joint, characterized in that the pulse arc welding is performed under the condition that the pulse rate ( / min) and pulse frequency f (Hz) satisfy the following formula (1). 0.15 ≤ 10 × W / f ≤ 1.00 ... (1)

2. The chemical composition of the weld metal is, in mass%, Sb: 0.01 to 0.50%, B: 0.0010-0.0100%, Cr: 0.01-0.80%, Ni: 0.01-1.00%, Mo: 0.001 to 0.200%, and V: 0.001~0.300% The manufacturing method according to claim 1, characterized by containing one or more selected from the group consisting of

3. The peak time T in the pulsed arc welding described above. p (milliseconds), rise time T up (milliseconds) and fall time T down The manufacturing method according to claim 1 or 2, characterized in that (milliseconds) satisfies the following formulas (2) and (3). T p >T up ≧T down ・・・(2) 1.0≦T up / T down ≦3.5 ・・・(3)

4. The peak current I in the pulsed arc welding described above p The current is 450-600A, and the base current I b The manufacturing method according to claim 1 or 2, characterized in that the amount is 55A or more.

5. A welded joint comprising a steel plate and a weld bead, The chemical composition of the weld metal forming the weld bead is, in mass%, C: 0.02-0.25%, Si: 0.02-1.50%, Mn: 0.30-3.50%, Ti: 0.04-0.25%, Al: 0.002-0.350%, O: 0.065% or less, N: 0.0350% or less, P: 0.030% or less, S: 0.020% or less, Sb: 0 to 0.50%, B: 0 to 0.0100%, Cr: 0-0.80%, Ni: 0 to 1.00%, Mo: 0-0.200%, V: 0-0.300%, and The remainder consists of Fe and impurities. On the weld bead-side surface of the aforementioned welded joint, the amount of spatter adhering to the weld bead peripheral region, where the length in the longitudinal direction extending along the weld bead is 50 mm and the length in the width direction perpendicular to the longitudinal direction and centered on the weld bead is 100 mm, is 2.0 spatter particles / cm². 2 A welded joint characterized by the following:

6. The chemical composition of the weld metal is, in mass%, Sb: 0.01 to 0.50%, B: 0.0010-0.0100%, Cr: 0.01-0.80%, Ni: 0.01-1.00%, Mo: 0.001 to 0.200%, and V: 0.001~0.300% The welded joint according to claim 5, characterized in that it contains one or more selected from the group consisting of the following.

7. The aforementioned sputter deposition amount is 1.0 particles / cm². 2 The welded joint according to claim 5 or 6, characterized in that it is as follows:

8. The aforementioned sputter deposition amount is 0.5 particles / cm². 2 The welded joint according to claim 5 or 6, characterized in that it is as follows:

9. The aforementioned sputter deposition amount is 0.1 particles / cm². 2 The welded joint according to claim 5 or 6, characterized in that it is as follows:

Citation Information

Patent Citations

  • Ultra-low silicon welding wire with excellent porosity resistance and electrodeposition coating properties, and weld metal obtained therefrom

    JP6829699B2

  • Pulse waveform search device, pulse waveform search method, pulse arc welding device, and pulse arc welding method

    JP7195993B2